Frequency of genesis and landfall of different categories of tropical cyclones over the North Indian Ocean - MOHAPATRA, MRUTYUNJAY; SHARMA, MONICA; DEVI, SUNITHA S.; KUMAR, S. V. J.; SABADE, BHARATI S. (MAUSAM, 2021)
India Meteorological Department (IMD) categorises the tropical cyclones (TCs) as cyclonic storm (CS), severe cyclonic storm (SCS), very severe cyclonic storm (VSCS), extremely severe cyclonic storm (ESCS) and super cyclonic storm (SuCS). The long term climatology of TCs in these categories and the trends in frequency and intensity of TCs in these categories developing over the NIO and crossing different coastal regions are limited. Hence a study has been undertaken to analyse the characteristics of genesis and intensification of CDs in the above categories developing over the NIO and crossing different coastal regions based on the data of satellite era (1965-2020). The most intense TCs (ESCS & above) cross the coast maximum over Odisha (ODS) followed by Andhra Pradesh (AP)/Myanmar (MMR) & Bangladesh (BDS) and low intensity TCs (CS/SCS) cross maximum over BDS followed by AP, ODS & Tamilnadu (TN) and medium intensity TCs (VSCS) cross maximum over TN/AP/BDS followed by ODS/West Bengal (WB)/MMR during a year as a whole. While maximum CS/SCS cross BDS, maximum VSCS cross BDS/MMR and maximum ESCS cross MMR coast during pre-monsoon season. While maximum CS/SCS/VSCS cross AP coast, maximum ESCS cross ODS coast during post monsoon season. Over the AS, the landfall frequency of VSCS is maximum over Arabia - Africa (AA) coast followed by Saurashtra and Kutch coast. The coastal vulnerability due to ESCS continues over the Bay of Bengal (BoB) region, as there is no significant trend in the frequency of genesis of ESCS and above intensity storms, though there is decreasing trend in the genesis frequency of D/DD, CS, SCS, VSCS over the BoB. It has increased over the AA coast due to increasing trend in frequency of genesis of VSCS and above intensity storms over Arabian Sea.